EFEKTIVITAS PEMBERIAN AIR REBUSAN JAHE TERHADAP EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I - DEVY LESTARI NURUL AULIA; ARUM DWI ANJANI; RISQI UTAMI; Berty Prima Lydia (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
Emesis gravidarum is a complaint that is often felt in the first trimester of pregnancy, this is due to hormonal changes, this can be Hyperemesis Gravidarum which can interfere with activity, nutritional disorders, electrolyte imbalance, dehydration and weight loss. Ginger boiled water is one of the non-pharmacological treatments for emesis gravidarum, the content of essential oils and gingreol in ginger can have a refreshing effect and inhibit the vomiting reflex. The purpose of this study was to determine the effectiveness of ginger boiled water against emesis gravidarum in first trimester pregnant women. This study was a pre-experimental study with a one group pretest-posttest design, conducted in July 2019 at the Tanjung Unggat Health Center. The population in this study were pregnant women in the first trimester who experienced emesis gravidarum with a total sample of 34 people. The research instrument used an observation sheet and analyzed with an independent T-test. The results showed that the average emesis gravidarum before being given ginger boiled water was 11.71 and the average emesis gravidarum after being given ginger boiled water was 5.12. The results of data analysis using paired sample t-test obtained p-value 0.000 (p <0.05), so Ho is rejected and it can be concluded that the administration of ginger boiled water is effective in reducing emesis gravidarum. Recommendations for health workers to be able to provide information to pregnant women about the method and dosage of ginger boiled water that is safe for consumption to reduce nausea and vomiting.